Energy Recovery for Commercial Aircraft During Landing - Deja, Jakub (Cranfield University, 2025)
This project explores advanced technologies for kinetic energy recovery in aviation, focusing on sustainable and efficient solutions for short-range aircraft operations. Given that such aircraft may perform up to thirteen flights per day, spending significant time taxiing, climbing, and descending, there is substantial potential to recover energy typically lost during braking on landing. A novel system coupling arresting gear with electrical generators was developed to recover this kinetic energy, demonstrating scalability across aircraft sizes and addressing integration challenges such as energy storage, safety, and passenger comfort. The research begins with the development of a sustainable arresting gear energy recovery system that captures kinetic energy during aircraft landing through coupling with electrical generators. This system demonstrates approximately 60% energy conversion efficiency with scalability across aircraft sizes from Airbus A319 to A380. Applied at a major hub like Heathrow Airport, such technology could generate approximately 17 GWh of electrical energy annually, equivalent to offsetting 6,367 metric tons of coal or 5,667 m of diesel fuel consumed in conventional power generation. Building on this foundation, a battery-powered landing gear drive system is designed to enable all-electric ground operations for narrowbody aircraft. Through integration of regenerative braking recovering 10% of landing energy, the system sup ports up to 26 minutes of electric taxiing via a 200 kWh modular battery architecture. Implementation analysis demonstrates 7% fuel consumption reduction for short-haul flights, with projections indicating potential savings of 500 kg fuel per flight by 2050 as component efficiencies improve. To facilitate efficient design optimization of these complex systems, the SPCrane framework is developed, introducing a pointwise ensemble surrogate modeling methodology that enhances prediction accuracy compared to traditional approaches. This computational innovation employs spatial adaptive weighting and sigmoid-based transition logic to improve boundary prediction stability, enabling more robust optimization of energy recovery systems. The research culminates in an electric machine braking system to replace conventional carbon-carbon composite brakes, utilizing a yokeless and segmented armature topology that achieves 120 Nm/kg torque density while enabling regenerative deceleration. Through electromagnetic-thermal co-design incorporating novel cooling strategies, the system meets performance requirements equivalent to commercial autobrake settings while withstanding extreme thermal gradients encountered during flight operations. Collectively, these innovations enable harvesting of wasted kinetic energy during typical short-haul operations while providing practical solutions toward more sustainable aviation within existing operational frameworks. The integrated technological solutions represent a comprehensive approach to reducing aviation’s environmental impact while maintaining performance and safety requirements essential for commercial aircraft operations.
Keywords: Energy recovery; Energy harvesting; Landing gear; Electric taxiing; Brake system; Arresting gear; ground operations